2001
DOI: 10.1046/j.1523-1739.2001.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Biology Framework for the Release of Wild-Born Orphaned Chimpanzees into the Conkouati Reserve, Congo

Abstract: Returning confiscated animals to their native habitats is desirable when it makes a positive contribution to the conservation of the species. Release of captive individuals is complex and controversial, however, particularly when risks are potentially high, as in the case of orphaned apes. We describe the decision-making process that led to the successive release of 20 wild-born orphan chimpanzees ( Pan troglodytes troglodytes ) into the Conkouati Reserve in the Republic of Congo. Recommendations of the Reintr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 19 publications
1
50
0
Order By: Relevance
“…This is comparable to Wimberger et al [2010] who reported an average survival rate of 33.5% after 10 months. As with Color version available online previous studies of rehabilitated primates [Suarez et al, 2001;Tutin et al, 2001;Wimberger et al, 2010], missing animals were an issue and their fate remains unknown. If missing animals are presumed dead, the mortality rate may have been as high as 68% over 12 months, considerably higher than the average reported rate of 22% per year in the wild population of vervet monkeys in Amboseli National Park, Kenya [Isbell, 1990].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is comparable to Wimberger et al [2010] who reported an average survival rate of 33.5% after 10 months. As with Color version available online previous studies of rehabilitated primates [Suarez et al, 2001;Tutin et al, 2001;Wimberger et al, 2010], missing animals were an issue and their fate remains unknown. If missing animals are presumed dead, the mortality rate may have been as high as 68% over 12 months, considerably higher than the average reported rate of 22% per year in the wild population of vervet monkeys in Amboseli National Park, Kenya [Isbell, 1990].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we suggest a community outreach programme as recommended by the IUCN [Baker, 2002], involving both rehabilitation centres and the government, to attempt to raise awareness about wildlife protection and to reduce the impacts of illegal hunting in protected areas in South Africa. Strategies to avoid conflict with humans in other primate release projects have included selection of a release site isolated from humans [de Silva, 1971;King et al, 2005], and exclusion of habituated animals from release [Tutin et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…Reintroduction is an increasingly common, although often controversial, tool in the conservation of endangered species (Fischer and Lindenmayer 2000;Griffith et al 1989;Sarrazin and Barbault 1996;Seddon et al 2007;Tutin et al 2001;Wolf et al 1996). Postrelease monitoring is an important aspect of reintroduction projects (Beck et al 2007;IUCN 2002;Seddon 1999), the results of which can be used to answer many questions related to the reintroduction project itself, to the focal species as a whole, or to general ecological principles (Armstrong and Seddon 2008;Nicoll et al 2003;Parker 2008;Sarrazin and Barbault 1996;Seddon et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the behaviour of individuals and the social system of species seems therefore crucial for the success of reinforcement projects (Lonsdorf 2007). As an example, reintroductions of male chimpanzees into wild populations often failed due to the high aggressiveness of resident males towards them (Tutin et al 2001), whereas releasing young females is more successful, as they are less likely to be attacked by residents or to disturb local populations (Goossens et al 2005). We cannot exclude the possibility that the introduction of young, immature field voles would have induced different responses from residents.…”
Section: Discussionmentioning
confidence: 99%